Inverse design and accurate optimization of layered structured seeding mechanism for sugarcane planters - Liu, Jiaodi; Chen, Qingli; Xu, Hongzhen; Hua, Yong; Wu, Xiaoman (International Journal of Agricultural and Biological Engineering, 2024)
Existing sugarcane planters are difficult to have ideal seeding trajectory and motion attitude at the same time, and the speed is difficult to meet the requirements at the critical stage, resulting in poor stability, which ultimately makes it impossible to ensure that the sugarcane seeding is carried out in accordance with the agronomic requirements to ensure that the cane buds are oriented toward the wall of the seeding trench. Aiming at the second-order non-circular planetary gear system pendulum seeding mechanism of the planter, the paper innovatively adopts the combination of inverse design and multi-objective layered accurate optimization to solve the problems of attitude, speed and trajectory that do not meet the requirements of fixed-attitude seeding that still exists in the process of sugarcane seeding. The second-order non-circular planetary gear system is simplified into a three-rod two-degree-of-freedom mechanism, and the radius of the pitch curve of each non-circular gear is solved inversely by actively preplanning the static trajectory of the cane seed motion and analyzing the law of motion of the rod assembly. Determining the range of cane seed attitude angles in different motion phases as the first layer optimization objective, and fine-tuning the position of static trajectory key type value points to achieve the first layer optimization. Based on the non-circular gear pitch curve obtained from optimization, the interpolation points are marked on each non-circular gear pitch curve of the second-order non-circular planetary gear system, and based on the parameter optimization method of human-computer interaction, the radius values corresponding to the interpolation points of the non-circular gear pitch curve are fine-tuned to optimize the pitch curves, so as to satisfy the speed requirements of the cane species in each stage, and at the same time to make the convexity of non-circular gears in line with the principle of gear mesh, so as to complete the second layer of accurate optimization. The results of simulation verification show that the motion trajectory attitude of the virtual prototype is basically consistent with the theoretical model, which verifies the feasibility of the mechanism design. This study provides a new optimized design method for the cane seeding mechanism of sugarcane planters to achieve directional seeding. Keywords: sugarcane planting, seeding mechanism, inverse design, layered structure optimization DOI: 10.25165/j.ijabe.20231606.8208 Citation: Liu J D, Chen Q L, Xu H Z, Hua Y, Wu X M. Inverse design and accurate optimization of layered structured seeding mechanism for sugarcane planters. Int J Agric & Biol Eng, 2023; 16(6): 107–115. directional seeding.